2006
DOI: 10.1590/s1020-49892006000600006
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin skin reactivity after neonatal BCG vaccination in preterm infants in Minas Gerais, Brazil, 2001-2002

Abstract: BCG vaccination could be recommended for preterm infants upon discharge from the neonatal unit to reduce morbidity and mortality in infants at risk for tuberculous infection, and to increase BCG vaccination coverage rates, especially in countries with high prevalence rates of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…[ 7 ] Higher scar failure rate (55%) has been reported in low birth weight babies from India. [ 8 ] A study from Pakistan reported scar failure rate of 19.6%,[ 3 ] whereas the studies from LIMA Peru,[ 1 ] Nigeria,[ 4 ] and Brazil[ 9 ] showed much lower scar failure rate of 1.4%, 3.7% and 3.1%, respectively. This difference could be accounted for by variability in the study design and differences in the demographic characteristics of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] Higher scar failure rate (55%) has been reported in low birth weight babies from India. [ 8 ] A study from Pakistan reported scar failure rate of 19.6%,[ 3 ] whereas the studies from LIMA Peru,[ 1 ] Nigeria,[ 4 ] and Brazil[ 9 ] showed much lower scar failure rate of 1.4%, 3.7% and 3.1%, respectively. This difference could be accounted for by variability in the study design and differences in the demographic characteristics of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Higher tuberculin conversion rates (80–93%) were observed in other studies. [ 9 13 14 15 ] Thayyil Sudhin reported tuberculin conversion to be 80% in term infants and 80.7% in preterms. [ 16 ] On the contrary, a low TST positivity (44–68%) was observed by many investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil ini hampir sama dengan penelitian yang dilakukan Sudhan dkk 9 yang mendapatkan (5,27±1,8) mm untuk bayi preterm yang segera di vaksinasi BCG dan (5,26±1,6) mm pada bayi preterm yang ditunda BCG sampai cukup bulan (38-40 minggu) Namun masih dibawah bila dibandingkan dengan Ferreira AA 13 yang mendapatkan rerata diameter indurasi tuberkulin pada bayi BBLR segera divaksinasi BCG segera setelah lahir (9,5±5,1) mm dibandingkan (9,6±5,0) mm pada bayi BBLC (berat badan lahir cukup) sebagai kontrol. Sementara itu di Brazil Camargos P dkk 16 (2002) melaporkan (6,8±4,70) mm untuk bayi preterm dan (10,2±4,53) mm bayi BBLC, terdapat perbedaan diameter indurasi yang cukup lebar antara kedua kelompok.…”
Section: Cara Kerjaunclassified
“…15 Penelitian Sudhan dkk 9 (1997) mendapatkan hasil tidak terdapat perbedaan konversi tuberkulin antara bayi preterm yang divaksinasi BCG segera saat lahir (80%) dengan yang ditunda sampai cukup bulan (38-40 minggu) (80,7%). Sedangkan penelitian terbaru yang dilakukan oleh Camargos P dkk 16 di Brazil mendapatkan hasil konversi tuberkulin pada bayi BBLR 2000 gram-2499 gram yang divaksinasi BCG segera saat lahir 67,5% dan vaksinasi pada bayi-bayi cukup bulan 87,7%. Terdapat 20,2% perbedaan antara kedua kelompok (p=0,02).…”
Section: Cara Kerjaunclassified
“…Tuberculin skin test (TST) is currently the most commonly used test for evaluation of cell-mediated immune response to Mycobacterium tuberculosis (8). Many studies suggest that preterm infants take up their BCG vaccination as efficiently as term neonates (9)(10)(11). However, there are conflicting results (12) and BCG scar formation in a large cohort of vaccinated infants including very low birth weight babies and preterms < 32 weeks gestation.…”
Section: Introductionmentioning
confidence: 99%